2020
DOI: 10.1021/acs.est.0c02888
|View full text |Cite
|
Sign up to set email alerts
|

Novel Perfluoroalkyl Ether Carboxylic Acids (PFECAs) and Sulfonic Acids (PFESAs): Occurrence and Association with Serum Biochemical Parameters in Residents Living Near a Fluorochemical Plant in China

Abstract: Although perfluoroalkyl ether carboxylic (PFECAs) and sulfonic acids (PFESAs) have been widely detected in environmental matrices, their occurrence in humans and impact on human health remains insufficiently understood. Here, we report on 13 PFECAs and PFESAs in 977 sera samples collected from residents living near a fluorochemical plant in Shandong, China. The sum concentration of these emerging PFECAs accounted for 13% of the total PFASs in the serum of the participants, with the frequent detection of severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
87
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 53 publications
(95 reference statements)
7
87
0
Order By: Relevance
“…Native standards of six emerging PFECAs, i.e., PFMOAA, PFO2HxA, PFO3OA, PFO4DA, PFO5DoDA, HFPO-TrA, and HFPO-TeA, were synthesized from their corresponding ethyl esters (Sanming Hexafluo Chemical Co., Ltd., China) following previously reported reactions. 17 Four PFECAs (i.e., HFPO-DA, PF4OPeA, PF5OHxA, PFO2HpA) were purchased from Wellington Laboratories (Guelph, ON, Canada). More details on standards and reagents are listed in Text S1.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Native standards of six emerging PFECAs, i.e., PFMOAA, PFO2HxA, PFO3OA, PFO4DA, PFO5DoDA, HFPO-TrA, and HFPO-TeA, were synthesized from their corresponding ethyl esters (Sanming Hexafluo Chemical Co., Ltd., China) following previously reported reactions. 17 Four PFECAs (i.e., HFPO-DA, PF4OPeA, PF5OHxA, PFO2HpA) were purchased from Wellington Laboratories (Guelph, ON, Canada). More details on standards and reagents are listed in Text S1.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Source temperature and ion-spray voltage can greatly impact the insource fragmentation of PFECAs. 17 Therefore, optimal conditions were screened from 12 × 15 combinations with 50 °C increments for the source temperature (50−600 °C) and 250 V increments for the voltage (1000−4500 V). When in-source fragmentation of PFECAs was effectively reduced under optimum conditions, an earlier strategy using secondary fragments (e.g., [M−H−CO 2 ] − and [M−H−CF 2 CO 2 ] − ) as "parent ions" was no longer needed 10,14,16 as sufficient signal strength could be obtained for [M−H] − ions.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…15,16 However, "alternative" PFAS containing −O−, [17][18][19] -H, 20,21 and -Cl 22,23 in the fluorinated moiety (RF) have also been systematically developed and extensively applied for decades. Recent studies have confirmed their negative health effects [24][25][26][27] and worldwide pollution in water [28][29][30][31][32][33][34][35][36] and soil. 37 Chlorine-containing PFAS (Clx−PFAS) are prepared by the telomerization process, where the iodinated telogen (RF−I) initiates the polymerization of fluorinated olefins (Schemes 1A and B).…”
mentioning
confidence: 95%